Determinants Of Student's Interest To Work In Islamic Entities - Marfuah Marfuah; Amanda Pramesti Nimaswara; Priyono Puji Prasetyo (LPPM ISNJ Bengkalis, 2023)
This study examines the effects of intrinsic work values, financial reward, work environment, professional training, professional recognition, social values, labor market considerations, personality, and spirituality on students’ interest in working in Islamic entities. The population of this study is 4,022 accounting students in the even semester of the 2021 academic year from four Islamic Universities in the special region of Yogyakarta. 148 students were selected as the research sample using the convenience sampling method. Based on the multiple linear regression analysis, the results of this study conclude that the intrinsic values of work, financial reward, and professional training have significant and positive effects on student’s interest in working in Islamic entities. The most dominant variable influencing students’ interest in working in Islamic entities is the intrinsic values of work. Meanwhile, work environment, professional recognition, social values, labor market considerations, personality, and spirituality do not affect students’ interest in working in Islamic entities. The results of this study contribute to Islamic entities to improve the system of employee recruitment to get the employees with the qualifications expected.